Should Auditors Owe a Duty to Stakeholders? (Journal of Governance and Development (JGD), 2012)
The traditional view in business law is that auditors should only owe their duties to a company since they are solely under a contractual relationship with the company. This is justified on the basis that it is the company which suffers loss if the auditors’ report is untrue. Nonetheless, it is trite to declare that stakeholders may also suffer a loss if the auditors’ report is untrue and it was relied upon. If the traditional view continues to be upheld, then the stakeholders will never be in a legally secured position as they cannot bring an action although the auditors’ report is untrue, there is reliance on and loss is suffered by the stakeholders. With this revelation, the auditors should also bear in mind the rights and interests of the stakeholders. This is because the information revealed by the auditors in their report is of fundamental importance to the stakeholders. Hence, this study examines to whom auditors owe their duty under the current legal position. The examination will unfold as to whether the scope of to whom auditors owe their duty is restrictive. The study will then investigate whether the auditors should owe their duty to stakeholders and the legal justifications for attaching such a duty. Notably, many fraudulent activities and ventures can be planned with the ingenious work and plan of the auditors. Therefore, the guiding principles for auditors should be responsibility and accountability. Arguably, this responsibility and accountability must be owed to a wider circle of persons and bodies, that is, the stakeholders.